Temperature Rise during Resin Composite Polymerization under Different Ceramic Restorations - Yondem, Isa; Altintas, Subutay Han; Usumez, Aslihan (European Journal of Dentistry, 2011)
Objectives: The purpose of this study was to measure temperature increase induced by various light polymerizing units during resin composite polymerization beneath one of three types of ceramic restorations. Methods: The resin composite (Variolink II) was polymerized between one of three different ceramic specimens (zirconium oxide, lithium disilicate, feldspathic) (diameter 5 mm, height 2 mm) and a dentin disc (diameter 5 mm, height 1 mm) with a conventional halogen light, a high intensity halogen light, or an LED unit. The temperature rise was measured under the dentin disc with a J-type thermocouple wire connected to a data logger. Ten measurements were carried out for each group. The difference between the initial and highest temperature readings was taken and the 10 calculated temperature changes were averaged to determine the mean value in temperature rise. Two way analysis of variance (ANOVA) was used to analyze the data (polymerizing unit, ceramic brand) for significant differences. The Tukey HSD test was used to perform multiple comparisons (α=.05). Results: Temperature rise did not vary significantly depending on the light polymerizing unit used (P=.16), however, the type of ceramic system showed a significant effect on temperature increases (P<.01). There were no statistically significant differences between lithium disilicate and feldspathic ceramic systems (P >.05); in comparison, the resin composite polymerized under the zirconium oxide ceramic system induced a significantly lower temperature increase than the other ceramic systems tested (P<.05) Conclusions: The resin composite polymerized beneath zirconium oxide ceramic system induced significantly smaller temperature changes. The maximal temperature increase detected in all groups in this study was not viewed as critical for pulpal health. (Eur J Dent 2011;5:305-309)
Keywords: Resin composite; Temperature; Ceramic restoration; Zirconium oxide